Advances in the study of FOXQ1: biological functions and mechanisms - Feng, Xiaojian; Zhang, Ling; Shi, Peiyao; Hu, Yiping (Frontiers in Oncology, 2025)
Forkhead box Q1 (FOXQ1) is a member of the Forkhead box gene family and an important transcription factor closely associated with several human diseases, especially tumorigenesis and tumor progression. This review aims to explore advances in the study of the biological functions of FOXQ1 in several tumors, such as colorectal cancer, breast cancer, esophageal cancer, nasopharyngeal cancer, lung cancer, hepatocellular cancer, pancreatic cancer, gastric cancer, melanoma, bone-related disease, immune and inflammatory disease, regulatory factors of FOXQ1 expression, and mechanism of tissue-specific function. FOXQ1 influences the pathological progression of these diseases through different targets genes and signaling pathways, which we also review in detail. In conclusion, more and more FOXQ1 applications and different pathologic mechanisms are bound to be reported in future studies.